2021
DOI: 10.1158/0008-5472.can-20-1659
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Condition the Therapeutic Efficacy of Trastuzumab in HER2-Positive Breast Cancer

Abstract: Running title: Gut microbiota implication in response to trastuzumab therapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 52 publications
(31 reference statements)
3
60
0
1
Order By: Relevance
“…Terrisse et al 62 found that chemotherapy drastically shifted the microbiome composition, by reducing abundance of microflora associated with side effects and increasing abundance of favorable commensals after adjuvant or neoadjuvant treatment with anthracylines and taxanes. A study by Di Modica et al 63 revealed the existence of specific microbiota in patients with Her2+ breast cancer that can influence their response to targeted therapy. This suggests that manipulation of the fecal microbiota is an optimal future regimen to achieve effective treatment or to explore its potential as a biomarker for therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Terrisse et al 62 found that chemotherapy drastically shifted the microbiome composition, by reducing abundance of microflora associated with side effects and increasing abundance of favorable commensals after adjuvant or neoadjuvant treatment with anthracylines and taxanes. A study by Di Modica et al 63 revealed the existence of specific microbiota in patients with Her2+ breast cancer that can influence their response to targeted therapy. This suggests that manipulation of the fecal microbiota is an optimal future regimen to achieve effective treatment or to explore its potential as a biomarker for therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…[103] Bacterial enzymes can degrade specific chemotherapy compounds into non-functional byproducts, [47] diminishing drug responses in colonized patients. In mouse models of HER2-positive breast cancer, antibiotic administration impairs trastuzumab efficacy and clinical patients with less diverse gut microbiomes are less likely to respond to trastuzumab; [68] moreover, fecal microbiota transplants from patient responders and non-responders into recipient mice recapitulate differential response to trastuzumab in patients, implicating gut microbiota as critical for HER2-targeted therapeutic responses. [68] Gut microbiota also affect hormonal therapies.…”
Section: Prognostics and Companion Diagnosticsmentioning
confidence: 99%
“…In mouse models of HER2-positive breast cancer, antibiotic administration impairs trastuzumab efficacy and clinical patients with less diverse gut microbiomes are less likely to respond to trastuzumab; [68] moreover, fecal microbiota transplants from patient responders and non-responders into recipient mice recapitulate differential response to trastuzumab in patients, implicating gut microbiota as critical for HER2-targeted therapeutic responses. [68] Gut microbiota also affect hormonal therapies. Administration of abiraterone acetate (AA) in the setting of castrate-resistant prostate cancer promoted outgrowth of Akkermansia muciniphila and appeared to aid overall AA therapeutic efficacy.…”
Section: Prognostics and Companion Diagnosticsmentioning
confidence: 99%
“…Recently, Di Modica et al analysed the gut microbiota composition of a group of breast cancer patients who responded favourably to adjuvant treatment with Trastuzumab. They found that in those patients with favourable results in response to treatment, Clostridiales ( Lachnospiraceae ), Bifidobacteriaceae , Turicibacteraceae, and Bacteroidales ( Prevotellaceae ) predominated, while in the other group of patients who did not respond to treatment, an enrichment in the phylum Bacteroidetes ( Bacteroidia ) was observed [ 95 ].…”
Section: Modulation Of Antitumoural Therapies Efficacy and Toxicity By Gut Microbiotamentioning
confidence: 99%